2006
DOI: 10.1021/jo061791b
|View full text |Cite
|
Sign up to set email alerts
|

Amberlite IRA900N3as a New Catalyst for the Azidation of α,β-Unsaturated Ketones under Solvent-Free Conditions

Abstract: Amberlite IRA900N3 is an excellent organocatalyst for the azidation of alpha,beta-unsaturated ketones with trimethylsilyl azide under solvent-free conditions. By avoiding the use of metallic species and of the organic reaction medium, the procedure is a green tool for the preparation of beta-azido ketones under mild conditions with yields from good to excellent. The catalyst can be recovered and re-used with no loss of its efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Therefore, in agreement to our previously reported results,8c it can be concluded that the reaction proceeds according to the plausible mechanism depicted in Scheme .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, in agreement to our previously reported results,8c it can be concluded that the reaction proceeds according to the plausible mechanism depicted in Scheme .…”
Section: Resultssupporting
confidence: 92%
“…According to our previous results,8ac the recovered catalysts resulted from the complete substitution of both fluoride ions by azido ions with formation of volatile trimethylsilyl fluoride, b.p. 16 °C.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The catalyst was recycled and reused in four more runs without loss of its efficiency and activity. 15 (B) Regio-and stereoselective bromoazidation of alkenes was carried out using N-bromosuccinimide (NBS) and TMSN 3 as bromine and azide source with good yields. Zinc triflate [Zn(OTf) 2 ] was an efficient catalyst for the synthesis of anti-1,2-bromoazide with high selectivity.…”
Section: Introductionmentioning
confidence: 99%